Cost minimization analysis of two chemotherapy regimens in the treatment of colorectal cancer in a public reimbursement hospital in Brazil - Sara C. BOSCATO (Sociedade Brasileira de Farmácia Hospitalar e Serviços de Saúde, 2021)
Objective: To conduct a pharmacoeconomic evaluation between XELOX and mFOLFOX6 in the adjuvant and metastatic treatment of colorectal cancer from the perspective of a public reimbursement hospital. Methods: The cost minimization analysis was conducted for patients who started treatment in 2013 and 2014. The micro-costing technique was used to verify expenditures on drugs, materials, laboratory and imaging tests, ambulatory and daily hospitalization, human and administrative resources and determine the individual cost of each alternative, per patient. To evaluate the robustness of the economic analysis, multivariate sensitivity analysis was performed in six different scenarios. Results: There was an average cost for XELOX of U$ 4,637.14 in adjuvant and U$ 3,831.48 for palliative treatment, and a cost for mFOLFOX6 of U$ 5,474.89 in adjuvant and U$ 4,432.95 in palliative treatment. Sensitivity analysis maintained the dominance of XELOX. Material and drug costs accounted for about 85% of the total cost of XELOX; for mFOLFOX6 this cost was around 36%. On the other hand, the cost of hospitalization and placement of a catheter occured exclusively for mFOLFOX6, which also presented a higher cost with human resources. Conclusion: From the perspective of the hospital, XELOX proved to be the least costly alternative on the treatment of colorectal cancer.